Extrusion parameters and physical transformations of an extrudate for fish: Effect of the addition of hydrolyzed protein flour from by-products of Oncorhynchus mykiss - Hoyos-Concha, José Luis; Villada-Castillo, Héctor Samuel; Roa-Acosta, Diego Fernando; Fernández-Quintero, Alejandro; Ortega-Toro, Rodrigo (Frontiers in Sustainable Food Systems, 2023)
Introduction The food industries play a fundamental role in feeding for the functions of animal metabolism. Fish feed extrusion cooking includes process-independent factors such as temperature (°C), screw speed (RPM), throughput, feed, and moisture content that influence the final product's nutritional value and physical properties. The evidence suggests that the application of hydrolyzed protein flour (HPH) is a crucial step for the techno-functional properties of the product. Therefore, this work aimed to study the effect of hydrolyzed protein meal from silage of trout (Oncorhynchus mykiss) on the parameters of the extrusion system and their physical transformations. Methods In this study, the influence of hydrolyzed protein meals ranges between 10 and 30% as a substitute for fish meals. The physical properties of the extrudate were monitored, evaluating the hardness, durability, buoyancy, expansion index, and apparent density. Results Consistent with this, parameters such as feed composition, screw speed, moisture content, and extrusion process affected the composition and properties of the final product. Discussion The physical properties indicated that the hydrolyzed protein flour presented cohesiveness and decreased the mean retention time in the extruder barrel and the specific mechanical energy (SME). Hydrolyzed protein flour during the extrusion process produces pellets with high durability and low hardness due to the high porosity presented, which allows for obtaining nutritional characteristics in the extruded product.